Bioengineered Gastrointestinal Tissue: Bioengineered Gastrointestinal Tissues with Fibroblast‐Induced Shapes (Adv. Funct. Mater. 6/2021). (3rd February 2021) - Zhou, Linna; Ruiz‐Puig, Carlos; Jacobs, Brittany‐Amber; Han, Xiaoyue; Lisle, Richard; Bayley, Hagan; Lu, Xin
Abstract : Bioengineered gastrointestinal tracts have potential applications both in regenerative medicine and disease modelling. In article number 2007514, Hagan Bayley, Xin Lu, and co‐workers produce collagen tubes with designed shapes by using a lipid bilayer supported droplet networks. Complex shapes are generated by controlling the seeding density of fibroblasts. Furthermore, when seeded with fibroblasts and epithelial cells, the tubular structures form sub‐epithelial and epithelial layers that line their lumens.